2007
DOI: 10.3844/ajassp.2007.251.256
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Moving Boundary Problem During Melting Process in a Rectangular Cavity Heated from Below

Abstract: Abstract:We present an analysis of the melting process in Phase Change Materials (PCM) in a horizontal cavity heated from below, driven by the coupling of transient heat conduction in the solid phase and steady state laminar natural convection in the liquid phase with one of the boundaries of the solution domain that moves. We state the problem in the Cartesian coordinate system; involve the use of a control volume method to solve the full vorticity equation together with the stream function and energy equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…This clearly indicates that the early stage of heat transfer is conduction controlled, whereas at a while convection heat transfer becomes to be dominant. Similar transition from conduction to convection in heat transfer is also observed when heating is applied at bottom of the enclosure of the PCM [159].…”
Section: Increasing Heat Transfer Surfacesmentioning
confidence: 52%
“…This clearly indicates that the early stage of heat transfer is conduction controlled, whereas at a while convection heat transfer becomes to be dominant. Similar transition from conduction to convection in heat transfer is also observed when heating is applied at bottom of the enclosure of the PCM [159].…”
Section: Increasing Heat Transfer Surfacesmentioning
confidence: 52%
“…The applications of the rectangular vessels can be found in nuclear reactors, solar energy systems, geothermal systems, etc. The rectangular or square designs used in LHTES systems are summarized in Table 1 32‐36 . Experiments and mathematical simulation of the effect of natural convection on the melting behavior of PCM in a rectangular vessel were performed by Lamberg et al 32 They found that the peak temperature of the PCM was achieved when the natural convection was absent.…”
Section: Configurations Of Lhtes Systems and Design Parametersmentioning
confidence: 99%
“…For the density measurements at the liquid state, the pycnometer is filled firstly with distilled water whose volume is defined in equation (3). Then, it is emptied, dried and filled with liquid paraffin until the stopper.…”
Section: Density Measurementsmentioning
confidence: 99%
“…They are classified into two groups according to the imposed boundary conditions: constant temperature, constant flux. Regarding to the first group, Jellouli et al [3] performed a numerical study of the melting process of a PCM with in a rectangular cavity heated from the bottom at a constant temperature. The natural convection was taken into account in the liquid PCM.…”
Section: Introductionmentioning
confidence: 99%